Pertanggungjawaban Pidana Terhadap Tindak Pidana Perdagangan Organ Tubuh Manusia Untuk Kepentingan Transplantasi Organ Dalam Hukum Pidana Indonesia - Romi Saputra; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Trafficking of human organs is one of the most rapidly evolving crimes in Indonesia.This crime is for the purpose of organ transplant effort. Transplantation is a noble undertakingwhere a donor gives a part of his body or his organs to help patients who have malfunction ofcertain organs. In Indonesia the criminal act of trafficking human organs by regulation.While the criminal acts of trafficking of human organs are extraordinary crimes thatshould be regulated more specifically in legislation such as laws on the trade of human organs.Based on this understanding, the writer of this thesis formulates two formulation of the problem,namely: First, How to regulate the criminal trafficking of human organs according to Indonesiancriminal law? Second, What is the criminal liability for the crime of trafficking of human organsin Indonesian criminal law?The regulation of the crime of trafficking of human organs based on positive law inIndonesia. Sanctions against criminals shall be subject to special sanctions that may bedeterrent such as imprisonment or fines.Based on this, Indonesia should make further rules on the criminal act of traffickinghuman organs into a form of legislation such as laws on the trading of human organs andpenalties by imposing appropriate sanctions on such crimes.Based on this, Indonesia shouldmake further rules on the criminal act of trafficking human organs into a form of legislation suchas laws on the trading of human organs and penalties by imposing appropriate sanctions onsuch crimes.